A rheumatology perspective on cutaneous vasculitis: assessment and investigation for the non‐rheumatologist. Issue 1 (26th March 2015) - Rawlings, Charlotte R; Fremlin, Georgina A; Nash, Julian; Harding, Keith
Abstract: Vasculitis, by definition, is inflammation of the vasculature. This inflammation can result in either vessel wall destruction causing aneurysm or rupture, or stenosis causing ischaemia or necrosis. This autoimmune response does not always have a clear cause. Vasculitis is a heterogeneous group of disorders that has been categorised not only by primary and secondary causes, but also by the size of the affected vessel. The secondary causes that can trigger vasculitis include infection (particularly hepatitis B and C and haemorrhagic fever);cancer, autoimmune diseases such as rheumatoid arthritis (RA), systemic lupus erythematosus (SLE) and Sjogren's; drugs or allergic reactions. As vasculitis can affect any part of the vasculature, it can result in a wide range of signs and symptoms. However, one of the most common presentations of vasculitis is a rash, due to small vessel vasculitis, which is most common. A vasculitic rash has certain characteristics that are easily identifiable and differentiate it from other rashes. This is a review from a rheumatologist's perspective of how to identify vasculitis skin changes. If cutaneous vasculitis is suspected, this article identifies other areas of skin that can be affected that need identification, in addition to what to screen for in the history and other differential diagnoses to consider. Subsequently, the article addresses the key investigations to request and a brief overview of the treatment principles for primary vasculitis.